ANALYSIS OF FACTORS INFLUENCING FOREIGN OWNERSHIP IN GOVERNMENT BONDS INDONESIA - Wati, Utami Aprilia; Prasetyo, Ahmad Danu (Journal of Business and Management, 2018)
Abstract.Â Indonesia is using a budget deficit policy in drafting a budget. The budget deficit is a policy where the government spending is planned greater than government revenue. To cover the deficit, government issue bonds. Compare with other countries in ASEAN, the proportion of foreign ownership in government bonds is the highest. However, a higher proportion of foreign ownership makes the risk of countries also higher. This research aims at providing empirical evidence on factors that affecting foreign ownership in Indonesia government bonds. The variables in this research consist of an internal factor, external factors, and combine factors during the period 2003M1 until 2017M12.The VECM test is used to test the hypothesis. Our result is all of the endogenous factors significantly affecting foreign ownership in Indonesia Government Bonds in the long-term period. Lagged three periods of foreign ownership, lagged two periods of 10-year Indonesia government bonds yield, the exchange rate of ringgit to US dollar, and 10-year Thailand government bonds yield have significantly affecting foreign ownership in Indonesia government bonds in the short-term period.Â Keyword: Exchange Rate, Foreign ownership, Government Bonds, VECM, yieldÂ